Mycobacterium Tuberculosis Infection and Inflammation: what is Beneficial for the Host and for the Bacterium? - Sasindran, Smitha J.; Torrelles, Jordi B. (Frontiers in Microbiology, 2011)
Tuberculosis is still a major health problem in the world. Initial interactions between Mycobacterium tuberculosis and the host mark the pathway of infection and the subsequent host inflammatory response. This inflammatory response is tightly regulated by both the host and the bacterium during different stages of infection. As infection progresses, the initial intense pro-inflammatory response observed is regulated by suppressive mediators balancing inflammation. In this environment, M. tuberculosis battles to survive interfering with the host inflammatory response. In this review we discuss the major effector molecules involved in inflammation in relation to the different stages of M .tuberculosis infection.